Effects of ultrasound on estradiol level, bone mineral density, bone biomechanics and matrix metalloproteinase-13 expression in ovariectomized rabbits - XIA, LU (Exp Ther Med, 2015)
The aim of the present study was to observe the effect of ultrasound (US) on estradiol level, bone mineral density (BMD), bone biomechanics and matrix metalloproteinase-13 (MMP-13) expression in ovariectomized (OVX) rabbits. A total of 28 virgin New Zealand white rabbits were randomly assigned into the following groups: Control (control group), ovariectomy (OVX group), ovariectomy with ultrasound therapy (US group) and ovariectomy with estrogen replacement therapy group (ERT group). At 8 weeks after ovariectomy, the US group received ultrasound treatment while the ERT group were orally treated with conjugated estrogens, and the control and OVX groups remained untreated. The estradiol level, BMD and bone biomechanics, cartilage histology and the MMP-13 expression were analyzed after the intervention. The results indicate that the US treatment increased estradiol level, BMD and bone biomechanical function. Furthermore, the US treatment appeared to improve the recovery of cartilage morphology and decreased the expression of MMP-13 in OVX models. Furthermore, the results suggest that 10 days of US therapy was sufficient to prevent the reduction of estradiol, BMD and bone biomechanical function, to protect osteoarthritis cartilage structure, and to reduce MMP-13 transcription and expression in OVX rabbits. Therefore, US treatment may be a potential treatment for postmenopausal osteoarthritis and osteoporosis.